2010
DOI: 10.1007/s00264-010-0958-z
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of Scarf osteotomy in hallux valgus

Abstract: We performed a retrospective study on 178 Scarf osteotomies with a mean follow-up of 44.9 months (range 15-83 months). Clinical rating was based on the forefoot score of the American Orthopaedic Foot and Ankle Society (AOFAS). Weight bearing X-rays were used to perform angular measurements and assess the first metatarsophalangeal joint (MTP 1). At follow-up the mean AOFAS score had improved significantly (p<0.001), but only 55% of the feet showed a perfect realignment of the first ray. Patients with a hallux v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 22 publications
1
41
1
6
Order By: Relevance
“…P revious studies have shown that the Scarf osteotomy achieves predictable results 3,[5][6][7][8]23,24 . However, none of those studies presented long-term, intermediate-term, and immediate postoperative results of the same patient cohort or reported the factors influencing long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P revious studies have shown that the Scarf osteotomy achieves predictable results 3,[5][6][7][8]23,24 . However, none of those studies presented long-term, intermediate-term, and immediate postoperative results of the same patient cohort or reported the factors influencing long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment of hallux valgus deformity includes an osteotomy of the first metatarsal bone (MT-I) and a softtissue procedure. The Scarf osteotomy, a midshaft osteotomy of the MT-I that is often performed in combination with a closingwedge osteotomy of the proximal phalanx of the big toe (Akin osteotomy 1 ), is one of the established methods [2][3][4][5][6][7][8][9][10] . The Scarf osteotomy is characterized by its "Z" shape (Figs.…”
mentioning
confidence: 99%
“…Over 130 different surgical techniques [1][2][3][4] to correct hallux valgus deformity have been proposed, although choosing the most appropriate treatment option continues to generate controversy [5][6][7][8][9][10][11]. The current trend is directed toward percutaneous procedures with the potential benefits of minimally invasive surgery [2], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This angle remained constant from the time of union to the last follow-up. The mean pre-operative HVA was 39 (range 21-52) degrees, and the mean postoperative HVA was 11.8 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) degrees. The mean HVA at the last followup was 12.7 (range 6-30) degrees.…”
Section: Resultsmentioning
confidence: 99%
“…Different types of proximal metatarsal osteotomies have been used over the last decades including proximal crescentic osteotomy [7], proximal chevron osteotomy [8,9], scarf osteotomy [10,11], Ludloff osteotomy [12], Mau osteotomy [13], modified Mau [14], lateral closing wedge basal osteotomy [15] and medial opening wedge basal osteotomy [16].…”
Section: Introductionmentioning
confidence: 99%